Interactions Between Therapeutic Proteins and Small Molecules: The Shared Role of Perpetrators and Victims. Issue 4 (29th June 2017) - Cavaco, M; Goncalves, J
Abstract : Therapeutic proteins (TPs) are becoming increasingly important as therapeutic agents. A consequence of expanding their clinical indications is coadministration with well‐established small‐molecule drugs (sMDs), which could lead to unpredictable effects. According to the existing regulatory guidance, the development of an sMD includes the evaluation of potential drug‐drug interactions (DDIs). For TPs, only a few drug interaction studies have been published. Limited clinically relevant models, long half‐lives, and complex elimination pathways are among the associated difficulties.